Improving Work Ability of Mentally Burdened Emerging Adults in Vocational Integration Programs: A Study Protocol - Sabatella, Filomena; von Wyl, Agnes (Frontiers in Psychology, 2019)
Background: Emerging adults who do not successfully transition from compulsory education to the upper secondary level are at increased risk of developing mental illness, as compared with their working peers. Early intervention is important in these cases; the course of an illness can be positively influenced if treated early and without delay, and consequently, the illness will not affect the professional and personal development of the emerging adults any further. In contrast, the longer that treatment of mental illness is postponed, the more significant the danger that the disease will become chronic. Up to now, vocational integration programs have been mostly educationally oriented. To recognize and treat mental illness in a timely way, we developed an intervention that includes psychotherapy support in a vocational integration program for emerging adults who have not successfully transitioned from compulsory education to the upper secondary level. Aim: The aim of this study is to investigate the effectiveness of the described intervention, which will be delivered to all emerging adults aged 16-29 entering the vocational integration program. Another objective is to determine, if it is worthwhile and feasible to proceed testing the intervention in a full-scale clinical trial. Conducting research with this population can be very difficult, making the need to test the feasibility of a clinical trial especially important. Methods: A single group clinical trial will be conducted to examine the effectiveness of the intervention described above. Emerging adults aged 16-29 entering a vocational integration program will be recruited. Participants will provide informed consent and complete pre-intervention measures and then, in addition to the regular vocational integration program, take part in the intervention group. The primary outcomes for this study are increase in work ability, mental health literacy, and mental health. Demographic information, vocational biography, and satisfaction with the intervention will also be collected. Questionnaire data will be collected at pre-intervention, post-intervention, and six-month follow-up. Ethics and dissemination: The Ethics Committee of the Canton of Zurich provided ethics approval for the study (2017-00936). The results will be object of future scientific publications and international conference presentations